1984
DOI: 10.1007/bf02409828
|View full text |Cite
|
Sign up to set email alerts
|

Computer technology for autistic students

Abstract: The first purpose of this article is to review the literature related to the use of computers with autistic individuals. Although only a limited number of applications have been reported, the potential of the computer to facilitate the progress of autistic persons is promising. The second purpose is to identify specific learning problems or styles associated with autism from the research literature and link these with the unique aspects of computer-based instruction. For example, the computer's role in improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

1988
1988
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 19 publications
1
37
0
3
Order By: Relevance
“…Those functions have been found to be successful for various computer-based interventions (e.g. Bernard-Opitz 1989;Panyan 1984;Yamamoto and Miya 1999). For instance, Chen and Bernard-Opitz (1993) found that 3 of 4 students with autism exhibited higher motivation to learn and fewer disruptive behaviors using computer-based instruction compared to more traditional personal instruction.…”
Section: The Current Studymentioning
confidence: 96%
See 1 more Smart Citation
“…Those functions have been found to be successful for various computer-based interventions (e.g. Bernard-Opitz 1989;Panyan 1984;Yamamoto and Miya 1999). For instance, Chen and Bernard-Opitz (1993) found that 3 of 4 students with autism exhibited higher motivation to learn and fewer disruptive behaviors using computer-based instruction compared to more traditional personal instruction.…”
Section: The Current Studymentioning
confidence: 96%
“…Chen and Bernard-Opitz 1993;Colby 1973;Faja et al 2008;Panyan 1984). Multisensory interactions, controlled and structured environments, use of multilevel interactive functions, and the ability to individualize instruction are some of the features that can assist children with ASD when working with computers.…”
Section: The Current Studymentioning
confidence: 98%
“…Although software design remains poorly documented, several experimental studies have shown the usefulness of computers for autism [18]. Psychopathologists express growing interest in using computers for special education of autistic people [19]. Besides that, parents were among the first to develop computerbased approaches for this purpose [20].…”
Section: Related Workmentioning
confidence: 99%
“…picture boards, communication devices) for children who remain essentially nonverbal. For those who show some verbal behavior (echolalic or productive), little that is specific to their problems has been done unless and until they begin reading [24,51,63]. The state of technology for language intervention defined more broadly includes many innovations, but little that addresses the needs of this population.…”
Section: Motivationmentioning
confidence: 99%